Targeting Dio3 to enhance mitophagy and ameliorate skeletal muscle wasting in sepsis - Gang Wang; Ming Chen; Yuheng Zhang; Dacheng Wang; Tao Gao; Jianfeng Duan; Huimin Lu; Minhua Cheng; Yun Xu; Xiaoyao Li; Yan Wang; Ke Cao; et al. (Redox Biology, 2025)
Recent studies highlight the role of skeletal muscle wasting in the sepsis-associated long-term mortality. Despite clinical recommendations for increased protein intake to counteract muscle wasting, the outcomes have been suboptimal, suggesting that anabolic resistance should be considered in addition to nutritional support. Emerging evidence suggests that impaired mitophagy hampers anabolic processes in skeletal muscle, exacerbating muscle wasting in sepsis. Furthermore, thyroid hormone (TH), which is essential for both anabolism and mitophagy, is locally inactivated by type 3 Deiodinase (Dio3) at the onset of sepsis, potentially disrupting mitophagy and contributing to anabolic resistance. Here we demonstrate that local hypothyroidism is a key factor impairing mitophagy in skeletal muscle during early sepsis, leading to metabolic disturbances and muscle wasting. Dio3 knockdown preserves muscle mass, and ameliorates metabolic dysfunction via mitophagy promotion in sepsis models. Mechanistically, the knockdown of Dio3 triggers an upregulation of NRK2, facilitating the restoration of NAD salvage synthesis. This enhancement of NAD levels subsequently activates Sirtuins deacetylase, which in turn decreases PINK1 acetylation, preventing its proteolytic processing by OMA1. Therefore, targeting Dio3 offers a promising therapeutic approach to counteract sepsis-induced muscle wasting.